Early Electroencephalographic Findings Correlate With Neurologic Outcome in Children Following Cardiac Arrest. Issue 7 (July 2016) - Ostendorf, Adam P.; Hartman, Mary E.; Friess, Stuart H.
Abstract : Objectives: To determine the clinical and electroencephalographic findings associated with prognosis in nonneonate children following cardiac arrest. Design: Retrospective observational study. Setting: PICU and cardiac ICU. Patients: Nonneonate children with a history of cardiac arrest more than 2 minutes. Interventions: Electroencephalographic monitoring within 72 hours of return of spontaneous circulation. Measurements and Main Results: Clinical and features, neurophysiologic data, and Pediatric Cerebral Performance Category scores were collected. Electroencephalographic traces were reviewed in a blinded manner, all seizures and electroencephalographic findings noted, and the electroencephalography was scored at 1 hour, 24 hours, and continuous electroencephalographic end. Discrete data regarding specific characteristics of the electroencephalographic background and seizures were studied. Univariate and multivariate analyses were performed to identify associations between clinical variables, electroencephalographic findings, and Pediatric Cerebral Performance Category score at hospital discharge. Multivariate analysis of 73 children revealed duration of cardiac arrest less than 20 minutes or continuous electroencephalographic background activity within 12 hours postreturn of spontaneous circulation were associated with good short term neurologic outcome. Change in electroencephalographic background score over time and electroencephalographic data collected after the initial hour were not associated with outcome. Conclusions: Following pediatric cardiac arrest, an initially normal electroencephalography or generalized slowing of the electroencephalographic background was associated with good neurologic outcome at hospital discharge.